A Web API for weather generation and pest development simulation in North America. (November 2022) - Fortin, Mathieu; Lavoie, Jean-François; Régnière, Jacques; Saint-Amant, Rémi
Abstract: Climate is an essential component of environmental models. Over the last two decades, many weather generators have been presented in the literature. Although their implementation into software has been of great help to environmental modellers, their lack of integration into modelling frameworks still represents a challenge for end users. In many cases, end users have to retrieve the climate variables by themselves in order to use an environmental model. In some other cases, the weather generator software is embedded into the modelling framework, but this increases the maintenance effort. In this paper, we present a different approach: the deployment of a weather generator as a Web API. A few application examples are provided to illustrate the benefits of this implementation. In summary, a Web API facilitates the integration into modelling frameworks, decreases the maintenance effort and avoid interoperability issues due to different programming languages.